Analysis design and experimental verification of a quadratic boost converter - Tattiwong, K.; Bunlaksananusorn, C. (My University, 2015)
This paper presents analysis, design and experimentation of a Quadratic Boost Converter (QBC). Operation of the QBC is analyzed, leading to mathematical expressions that can be used to design the converter. Based on the derived analytical expressions, a 100W, 12V-to-48V, QBC converter is designed and built. Experiment shows that the prototyped converter operates satisfactorily throughout its operating range and achieves the highest efficiency of 83%.
Keywords: Analysis; DC-DC converters; Design